UMP among the worlds top 150 young universities - Hazlina, Faizal (2020)
Pekan, 24 June 2020 - Universiti Malaysia Pahang (UMP) is listed among the 101–150 top universities under 50 years old in the QS Top 50 Under 50 ranking announced by the international ranking agency QS Quacquarelli Symonds recently.